Ascorbate-mediated regulation of growth, photoprotection, and photoinhibition in Arabidopsis thaliana - Plumb, William (J Exp Bot, 2018)
The requirements for ascorbate for growth and photosynthesis were assessed under low (LL; 250 µmol m(–2) s(–1)) or high (HL; 1600 µmol m(–2) s(–1)) irradiance in wild-type Arabidopsis thaliana and two ascorbate synthesis mutants (vtc2-1 and vtc2-4) that have 30% wild-type ascorbate levels. The low ascorbate mutants had the same numbers of leaves but lower rosette area and biomass than the wild type under LL. Wild-type plants experiencing HL had higher leaf ascorbate, anthocyanin, and xanthophyll pigments than under LL. In contrast, leaf ascorbate levels were not increased under HL in the mutant lines. While the degree of oxidation measured using an in vivo redox reporter in the nuclei and cytosol of the leaf epidermal and stomatal cells was similar under both irradiances in all lines, anthocyanin levels were significantly lower in the low ascorbate mutants than in the wild type under HL. Differences in the photosynthetic responses of vtc2-1 and vtc2-4 mutants were observed. Unlike vtc2-1, the vtc2-4 mutants had wild-type zeaxanthin contents. While both low ascorbate mutants had lower levels of non-photochemical quenching of chlorophyll a fluorescence (NPQ) than the wild type under HL, qP(d) values were greater only in vtc2-1 leaves. Ascorbate is therefore essential for growth but not for photoprotection.